Arsenic Removal from Water Using Industrial By-Products - Lekić, Branislava M.; Marković, Dana D.; Rajaković-Ognjanović, Vladana N.; Đukić, Aleksandar R.; Rajaković, Ljubinka V. (Journal of Chemistry, 2013)
In this study, removal of arsenic ions using two industrial by-products as adsorbents is represented. Removal of As(III) and As(V) from water was carried out with industrial by-products: residual from the groundwater treatment process, iron-manganese oxide coated sand (IMOCS), and blast furnace slag from steel production (BFS), both inexpensive and locally available. In addition, the BFS was modified in order to minimise its deteriorating impact on the initial water quality. Kinetic and equilibrium studies were carried out using batch and fixed-bed column adsorption techniques under the conditions that are likely to occur in real water treatment systems. To evaluate the application for real groundwater treatment, the capacities of the selected materials were further compared to those exhibited by commercial sorbents, which were examined under the same experimental conditions. IMOCS was found to be a good and inexpensive sorbent for arsenic, while BFS and modified slag showed the highest affinity towards arsenic. All examined waste materials exhibited better sorption performances for As(V). The maximum sorption capacity in the batch reactor was obtained for blast furnace slag, 4040 μgAs(V)/g.